2021
DOI: 10.3906/sag-2009-270
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of systemic involvement of Coronavirus disease 2019 through spleen; size and texture analysis

Abstract: Aim: To investigate the changes in the spleen size, parenchymal heterogeneity, and computed tomography (CT) texture analysis features of patients diagnosed with Coronavirus Disease 2019 (COVID-19) Methods: The size and parenchymal structure of the spleen in 91 patients who underwent thoracic CT examination due to COVID-19 were evaluated. For the evaluation of parenchymal heterogeneity, CT texture analysis was performed using dedicated software (Olea Medical, France). The texture analysis of each case consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…However, the consistency of HU values was maintained. The radiomics analysis from the study was even more enlightening, revealing discernible discrepancies in various splenic features, hinting at alterations in the parenchymal microstructure of the spleen [ 11 ]. This evidence brings forth the contention that the spleen could be systematically impacted by COVID-19, thus presenting it as a potential target organ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the consistency of HU values was maintained. The radiomics analysis from the study was even more enlightening, revealing discernible discrepancies in various splenic features, hinting at alterations in the parenchymal microstructure of the spleen [ 11 ]. This evidence brings forth the contention that the spleen could be systematically impacted by COVID-19, thus presenting it as a potential target organ.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence brings forth the contention that the spleen could be systematically impacted by COVID-19, thus presenting it as a potential target organ. The swift transformation in spleen size and its microstructural facets elevates the importance of further probing into the long-lasting implications of the virus on splenic health [ 11 ]. Aksu et al further reinforced the argument of splenic involvement in COVID-19, linking splenomegaly in patients with COVID-19-induced pneumonia to an increase in lung abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the regression coefficient of waveletHLL_ngtdm_coarseness was -23.616, which indicated that the more uniform GGO the lower the probability of invasiveness. Firstorder_Maximum is the maximum grey intensity in the region of interest ( 43 ). The regression coefficient of waveletLHH_firstorder_Maximum was -0.007, which indicated that the smaller the maximum grey intensity of GGO the higher the probability of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a specific tropism for the vascular system, direct infection of the lymphatic organs such as the spleen with SARS-CoV-2 has been shown 2 3. Imaging findings range from a significant increase in the size of the spleen in the early stage of infection4 to a size reduction over time 5 6. Complications of splenic involvement in COVID-19 often present as solitary or multifocal splenic infarction 7 8.…”
Section: Introductionmentioning
confidence: 99%